Pelvic floor muscle training in men with post-prostatectomy urinary incontinence: a scoping review - Jackelline Evellin Moreira dos Santos; Virginia Visconde Brasil; Cissa Azevedo; Lívia Cristina de Resende Izidoro; Anna Julia Guimarães Batista; André Carlos Santos Ferreira; Luciana Regina Ferreira da Mata (Revista Latino-Americana de Enfermagem)
Objective: to map pelvic floor muscle training protocols available in the literature for the management of post-prostatectomy urinary incontinence. Method: this is a scoping review conducted in six databases. Information retrieval was performed using a specific instrument, including: title, authorship, year of publication, journal, objective, study design and description of the protocols’ content. Results: a total of 24 studies were included, which resulted in different protocols. The most frequent recommendations were the following: three sessions per day; with a frequency of six to 15 contractions per session; performing the exercises in the lying, sitting, and standing positions. The most cited guidelines in the protocols were anal sphincter and bulbocavernosus muscle contractions. All protocols followed the principle of regular pelvic floor muscle contraction, but there was no consensus regarding the start of the protocol, treatment duration, contraction/relaxation time, and intensity of the contraction force. Conclusion: different orientations were found in the pelvic floor muscle training protocols post-prostatectomy urinary incontinence, with emphasis on contraction time, relaxation time, number of contractions per session, training position, and protocol duration time. Different concepts were adopted to define urinary continence in the protocols. It is necessary to develop consensus guidelines that clearly define the parameters of training protocols.